Antibacterial Activity and Membrane-Targeting Mechanism of Aloe-Emodin Against Staphylococcus epidermidis - Li, Tao; Lu, Yan; Zhang, Hua; Wang, Lei; Beier, Ross C.; Jin, Yajie; Wang, Wenjing; Li, Huanrong; Hou, Xiaolin (Frontiers in Microbiology, 2021)
The emergence of multidrug-resistant Staphylococcus epidermidis (S. epidermidis) dwarfs the current antibiotic development and calls for the discovery of new antibacterial agents. Aloe-emodin is a plant-derived compound that holds promise to battle against these strains. This work reports the antimicrobial activity of aloe-emodin against S. epidermidis and other Gram-positive pathogenic species, manifesting minimum inhibitory concentrations (MICs) and minimum bactericidal concentration (MBCs) around 4–32 and 32–128 μg/mL, respectively. For Gram-negative bacteria tested, the MICs and MBCs of aloe-emodin were 128–256 and above 1024 μg/mL, respectively. Aloe-emodin at the MBC for 4 h eradicated 96.9% of S. epidermidis cells. Aloe-emodin treatment led to deformities in the morphology of S. epidermidis cells and the destroy of the selective permeability of the cell membranes. Analysis of the transcriptional profiles of aloe-emodin-treated cells revealed changes of genes involved in sulfur metabolism, L-lysine and peptidoglycan biosynthesis, and biofilm formation. Aloe-emodin therefore can safely control Gram-positive bacterial infections and proves to target the bacterial outer membrane.